Genetic diversity of ex-situ conserved Arabica cofee (Coffea arabica L.) accessions in Ethiopia as revealed by simple sequence repeats markers (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2023)
So far, there has been limited use of molecular markers in arabica coffee breeding program in Ethiopia. The objectives of this study were to explore the effectiveness of simple sequence repeats markers (SSRs) in detecting polymor- phism and to assess the extent of genetic diversity and relationships among ex-situ conserved Arabica coffee accessions. Sixty-two forest coffee accessions planted in the experimental plot of the Ethiopian coffee breeding program were evaluated using 14 SSR markers. These markers amplified a total of 100 alleles, varying from four to ten alleles per locus, with an average of 7.2 across all loci. The rate of polymorphism ranged from 75 to 100, with a mean value of 96.4 across the accessions. The polymorphic information content (PIC) varied from 0.26 to 0.92, with a mean value of 0.70. The genetic similarity coefficient values between 72% possible pair-wise combinations ranged from 0.18 to 0.50, with overall mean value of 0.44. The unweighted pair group method with arithmetic mean (UPGMA) dendrogram based on Jaccardâ€™s genetic similarity grouped the accessions into five main clusters and two singletons at